The Effect of Polyphenols on Working and Episodic Memory in Non-pathological and Pathological Aging: A Systematic Review and Meta-Analysis - de Vries, Karin; Medawar, Evelyn; Korosi, Aniko; Witte, A. Veronica (Frontiers in Nutrition, 2022)
Life expectancy steadily increases, and so do age-associated diseases, leading to a growing population suffering from cognitive decline and dementia. Impairments in working memory (WM) and episodic memory (EM) are associated with an increased risk of developing dementia. While there are no effective pharmacological therapies to preserve or enhance cognition and to slow down the progression from mild memory complaints to dementia so far, plant-based nutrients including polyphenols have been suggested to exert beneficial effects on brain aging. This review studies whether supplementary polyphenols are effective in preserving or enhancing memory in both non-pathological and pathological aging, and whether there are polyphenol efficiency differences between WM and EM. A systematic literature search was conducted and 66 out of 294 randomized clinical trials with 20 participants or more per group, aged 40 years or older were included. These covered a daily intake of 35–1,600 mg polyphenols, e.g., flavonols, flavonoids, isoflovones, anthocyanins, and/or stilbenes, over the course of 2 weeks to 6.5 years duration. In total, around half of the studies reported a significantly improved performance after polyphenol administration compared to control, while three studies reported a worsening of performance, and the remainder did not observe any effects. According to pooled WM and EM meta-analysis of all memory outcomes reported in 49 studies, overall effect size for WM and EM indicated a significant small positive effect on EM and WM with similar estimates (b ~ 0.24, p < 0.001), with large study heterogeneity and significant Funnel asymmetry tests suggesting a positivity bias. These results remained similar when excluding studies reporting extremely large positive effect sizes from the meta-analyses. While Ginkgo biloba and isoflavones did not show benefits in subgroup meta-analyses, those suggested some effects in extracts containing anthocyanins, other flavonoids and resveratrol, again potentially resulting from publication bias. To conclude, a systematic review and meta-analysis indicate that short- to moderate-term polyphenol interventions might improve WM and EM in middle-to older aged adults, however, publication bias in favor of positive results seems likely, rendering definite conclusions difficult. Future studies with larger, more diverse samples and sensitive monitoring of cardiovascular, metabolic and beginning brain pathologies as well as longer follow-up are needed to better understand the impact of age, (beginning) pathologies, gender, and long-term use on polyphenol action.